2006
DOI: 10.1111/j.1365-2362.2006.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol (–)‐epigallocatechin‐3‐gallate inhibits ethanol‐induced activation of pancreatic stellate cells

Abstract: Our results suggest that green tea and polyphenols could prevent pancreatic fibrosis by inhibiting PSC activation through the antioxidative effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…In a recent study, Masamune et al (2006) have demonstrated that curcumin, the yellow pigment in curry, inhibits PSC proliferation. Furthermore, other groups provided evidence that compounds like statins, taurine, or the green tea extract epigallocatechin gallate could also block the proliferation of PSCs in experimental in vitro or in vivo models, but the exact cellular mechanisms are still not fully understood (Jaster et al, 2003;Asaumi et al, 2006;Shirahige et al, 2007). Note that all of these mentioned substances are potent inducers of the cytoprotective enzyme HO-1 in several cell types, but no information is available concerning their effects on HO-1 in the pancreas (Olszanecki and Marcinkiewicz, 2004;Wu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Masamune et al (2006) have demonstrated that curcumin, the yellow pigment in curry, inhibits PSC proliferation. Furthermore, other groups provided evidence that compounds like statins, taurine, or the green tea extract epigallocatechin gallate could also block the proliferation of PSCs in experimental in vitro or in vivo models, but the exact cellular mechanisms are still not fully understood (Jaster et al, 2003;Asaumi et al, 2006;Shirahige et al, 2007). Note that all of these mentioned substances are potent inducers of the cytoprotective enzyme HO-1 in several cell types, but no information is available concerning their effects on HO-1 in the pancreas (Olszanecki and Marcinkiewicz, 2004;Wu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin-3-gallare (EGCG) 76 is an antioxidant polyphenol purifi ed from green tea and curcumin, 77 and it is a major component of turmeric. The polyphenol family has anti-infl ammatory, antifi brotic, and anticancer properties.…”
Section: Polyphenolmentioning
confidence: 99%
“…A similarly low level of evidence exists for green tea and green tea extracts. Animal models show a protective effect of green tea polyphenols and aqueous extracts from green and black tea [47,48], but no convincing clinical trial or epidemiologic data supporting this effect in humans are currently available.…”
Section: Chronic Pancreatitismentioning
confidence: 99%